The loss of journalistic information value: causes and consequences - Casero-Ripollés, Andreu (Anuario ThinkEPI, 2014)
The exchange value of journalistic information is deteriorating. This phenomenon affects both the industrial basis and the social and democratic functions of journalism. This paper analyses the causes and effects. The first is related to the abundance of information, the lack of credibility and the absence of a solid digital business model. The second suggests a scenario accentuated by the reduction of quality, the fragility of journalistic business, the concentration of the audience, the weakening of the journalistic profession, and less social relevance. These effects suggest the need to explore new channels to recover the value of journalistic information in the digital scenario.
Keywords: Journalistic information; Digital journalism; Business model; Journalistic business.